TI_GERICHTE 90.2015.123 vom 12. Juli 2017 , Revisione di un piano regolatore - mantenimento di una parte di un fondo in zona agricola - TI Tribunale d'appello (2017)
Revisione di un piano regolatore - mantenimento di una parte di un fondo in zona agricola